Anti-inflammatory chemoprevention attenuates the phenotype in a mouse model of esophageal adenocarcinoma. (20th April 2021) - Baumeister, Theresa; Ingermann, Jonas; Marcazzan, Sabrina; Fang, Hsin-Yu; Oellinger, Rupert; Rad, Roland; Engleitner, Thomas; Kleigrewe, Karin; Anand, Akanksha; Strangmann, Julia; Schmid, Roland M; Wang, Timothy C; et al.
Abstract: Barrett's esophagus (BE) is the main known precursor condition of esophageal adenocarcinoma (EAC). BE is defined by the presence of metaplasia above the normal squamous columnar junction and has mainly been attributed to gastroesophageal reflux disease and chronic reflux esophagitis. Thus, the rising incidence of EAC in the Western world is probably mediated by chronic esophageal inflammation, secondary to gastroesophageal reflux disease in combination with environmental risk factors such as a Western diet and obesity. However, (at present) risk prediction tools and endoscopic surveillance have shown limited effectiveness. Chemoprevention as an adjunctive approach remains an attractive option to reduce the incidence of neoplastic disease. Here, we investigate the feasibility of chemopreventive approaches in BE and EAC via inhibition of inflammatory signaling in a transgenic mouse model of BE and EAC (L2-IL1B mice), with accelerated tumor formation on a high-fat diet (HFD). L2-IL1B mice were treated with the IL-1 receptor antagonist Anakinra and the nonsteroidal anti-inflammatory drugs (NSAIDs) aspirin or Sulindac. Interleukin-1b antagonism reduced tumor progression in L2-IL1B mice with or without a HFD, whereas both NSAIDs were effective chemoprevention agents in the accelerated HFD-fed L2-IL1B mouse model. Sulindac treatment also resulted in a marked change in the immune profile of L2-IL1B mice. In summary, anti-inflammatory treatment of HFD-treated L2-IL1B mice acted protectively on disease progression. These results from a mouse model of BE support results from clinical trials that suggest that anti-inflammatory medication may be effective in the chemoprevention of EAC. Abstract : We investigated anti-inflammatory treatment with Anakinra, Aspirin (acetylsalicylic acid, ASA) or Sulindac as chemopreventive approach in a genetic mouse model of Barrett's esophagus. The overall protective effect of the treatments suggests anti-inflammatory medication as promising chemoprevention approach in esophageal adenocarcinoma.